Impact of Social Media on Marriage Stability in Central Division Kabale Municipality Kabale District. - Ainembabazi, Georgianah (Kabale University, 2025)
The study assessed the impact of social media on the stability of families in Central Division, Kabale municipality. The study was guided by three objectives: to find out the effects of social media on marriage stability in Central Division, Kabale Municipality, to identify the challenges associated with the use of social media networks in Central Division, Kabale Municipality, to suggest the possible measures to the negative effects of marriage in Central Division descriptive research and correlation designs that were based on survey method was employed. Both simple random and purposive sampling techniques were used in determining the sample size of respondents. The study findings revealed the effects of social media on marriage stability in Central Division, Kabale Municipality and these included opportunities for Infidelity, comparison and Unrealistic Expectations, distraction and Neglect, jealousy, and Trust Issues. The study findings indicated that the most reported effect, with 33.7% of respondents identifying jealousy and trust issues as a significant impact of social media on their marriage stability. The study also showed the challenges associated with the use of social media networks in the central division, Kabale Municipality and these included hacking, anxiety and Depression, cyberbullying and Harassment, misinformation and Fake News, technical challenges, privacy, and security. The study findings indicated that Hacking is identified by 21.2% of respondents as a significant challenge associated with social media use. The results also indicated the possible measures for the negative effects of social media on marriage in Central Division and these included marriage Education Programs, Stress Management Techniques, Social Support Networks, and preventative counseling. The study findings indicated that preventative counseling is identified by 33.7% of respondents as a key measure to mitigate the negative effects of social media on marriage.